(untitled) - Jerrold L Wagener (New York, 1980)
This book is a comprehensive text/reference on Fortran programming, and completly describes the new standard Fortran language - Fortran 77. It is divided into three major parts: Part one includes I/O, the declaration and use of data elements in problem solving, selection and repetition control structures, and ends with an introduction to program modularization (subroutines). Part two deals with the structuring of programs and related aspects of programming and program development. Part three deals with data elements and Fortran's facilities for representing and processing data
Keywords: fortran 77 ( computer program language ),programming languages ( electronic computers )